2020
DOI: 10.1002/slct.202002714
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Phosphate and ATP by Lanthanide Complexes in Aqueous Medium and Its Application on Living Cells

Abstract: The design of coordination complexes as synthetic receptors for selective sensing of inorganic anions and nucleoside phosphates in aqueous medium under physiological conditions are important for biomedical research and drug delivery. In this work, two phenanthroline-based luminescent lanthanide complexes; EuLCl 3 (1) and TbLCl 3 (2), were explored for sensing anions such as HPO 4 2À , SO 4 2À , CH 3 COO À , I À , Br À , Cl À , F À , NO 3 À and HSO 4 À with HPO 4 2À exhibiting the strongest emission. Nucleoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Since the antenna effect is extremely interesting from fundamental point of view, many theoretical and spectroscopic studies discussed the photophysical process of absorption of light, the excited state energy transfer from the ligand to the europium ion and the luminescent properties of these compounds [ 30 , 31 , 32 , 33 , 34 ]. Application-oriented investigations on phenanthroline-based complexes also demonstrated their importance for the advance technologies [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the antenna effect is extremely interesting from fundamental point of view, many theoretical and spectroscopic studies discussed the photophysical process of absorption of light, the excited state energy transfer from the ligand to the europium ion and the luminescent properties of these compounds [ 30 , 31 , 32 , 33 , 34 ]. Application-oriented investigations on phenanthroline-based complexes also demonstrated their importance for the advance technologies [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, complex 85 was used as a staining agent in live green algal cells. 126 Nadella et al reported a series of phenanthroline-based hexadentate ligands with two chiral imine moieties and their corresponding lanthanide complexes with various lanthanide ions such as La( iii ), Eu( iii ), Tb( iii ), Lu( iii ), and Y( iii ) metal ions with a coordination number nine. The crystal structures of these complexes [ML 1 Cl 3 ] (M = La( iii ), Eu( iii ), Tb( iii ), Lu( iii ), or Y( iii )) were also reported.…”
Section: Chemosensors For the Detection Of Atpmentioning
confidence: 99%
“…There is a pressing need to remove phosphate from aqueous solution, otherwise it can raise the possibility of aquatic ecosystem eutrophication. [2][3] In recent decades, chemical, physical, biological, and other techniques have been conducted to reduce phosphate from wastewater. [4][5] By comparison, adsorption is relatively economical and effective due to its simple remove process and low energy equipment.…”
Section: Introductionmentioning
confidence: 99%